Some Aspects of Corrosion Resistance of Magnesium Alloys - E. Ghali (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
For engineering applications, magnesium is usually alloyed with one or more elements which include aluminium, manganese, rare earth metals, lithium, zinc, and zirconium. Under normal environmental conditions, the corrosion resistance of magnesium alloys is comparable or better than that of mild steel. The oxide film thickness on pure magnesium after exposure for only ?10 seconds at ambient temperature is 2.2 ± 0.3 nm. Exposure to humid air or to water leads to the formation of a thick hydrated amorphous film that has an oxidation rate less than 0.01 pm/ y. E-pH diagram and high temperature corrosion are discussed. The pH values between 8.5 and 11.5 correspond to a relatively protective oxide or hydroxide film that is more stable at higher pH. Structural applications of magnesium alloys are limited by creep strength rather than by oxidation. Active and active-passive behaviours of magnesium alloys are discussed. The pilling Bedworth Ratio values of oxide and hydroxide are 0.79 and 1.77 respectively and so the formation of Mg(OH)2 inside the oxide film could lead to the development of cracks. Microbiologically influenced corrosion and rational biodegradation of magnesium alloys are discussed because of their interest for medical care.